A Snapshot of Adverse Effects of General and Spinal Anaesthesia during Caesarean Section (IAHS Medical Journal, 2026)
Background: The number of caesarean section is increasing both in developed and developing countries. Anesthesia is must in cesarean delivery. This study aims to analyze the adverse effects of general and spinal anesthesia during cesarean section.Materials and methods: This prospective observational study included 60 pregnant women who had underwent cesarean section in IAHS Hospital, Chattogram. The ladies were categorized in two equal groups. One group included patients undergone general anesthesia and other group undergone spinal anesthesia during cesarean section. Data regarding socio demographic profile and adverse effects during cesarean section were recorded in a structured questionnaire and analysis was done by SPSS version 23.Results: The study revealed that majority 21(35%) and 18(30%) of the expectant mother who had undergone cesarean section with general anesthesia and spinal anesthesia respectively belonged to age group 18-25 years. Regarding adverse effects while using general anesthesia, out of 30 pregnant women, 6(20%) experienced hypotension, 20(66%) pain, 4(13.3%) infection, 14(46.6%) headache, 5(16.6%) vomiting and 4(13.3%) experienced fever. In case of using spinal anesthesia, out of 30 patients 8(26.6%) experienced hypotension, 14(46.6%) pain, 5(16.6%) infection, 20(66.6%) headache, 4(13.3%) vomiting and 4(13.3%) experienced fever.Conclusion: There are some unavoidable adverse effects in both general and spinal anesthesia while performing cesarean operation.IAHS Medical Journal Vol 8(1), June 2025; 32-34